Boko Haram Insurgency: Its Genesis, Recruitment Methods and Impact in Borno State - Ribadu, Hamza Tukur (NIU Journal of Humanities, 2023)
This article examines the genesis of the Boko Haram insurgency especially its doctrinal foundations and the fertile ground that made the group to thrive at the time that it emerged. Which included social exclusion, economic deprivation and environmental degradation. While the recruitment methods employed by the group included indoctrination, forceful conscription and inducement. However, the main outlook of the article is the impact of Borno Haram which demography, economic, religious and political aspects. These included loss of lives, destruction of infrastructures displacement of about 2 million people. The methodology employed is qualitative research in which content analysis and oral interviews are used. In conclusion, the Boko Haram group which started as a local proselytizing group metamorphosed into a monster that wreaked havoc on all aspects of the Borno society. It is recommended that to forestall the emergence of similar groups like the Boko Haram, the Nigerian State create job opportunities, engage the youth use learned scholars in countering violent ideologies.    Key w ords: Boko Haram insurgency, Genesis, Recruitment methods, Impact, Ideology